Effect of Probiotic Supplements on Egg Quality and Laying Hen`s Performance - Mahdavi, A.H.; Rahmani, H.R.; Pourreza, J. (International Journal of Poultry Science, 2005)
The effect of probiotic supplements (0, 400, 1000 and 2000 gr Bioplus 2B ton-1 feed providing 0, 1.28x106, 3.2x106 and 4.6x106 cfu gr-1 feed concentration) on egg quality and laying hen`s performance was investigated on eighty white leghorn Hy-Line, W-36 strain. Evaluated traits were egg production, egg weight, egg mass, feed consumption, feed conversion ratio, shell thickness, shell hardness, Haugh unit,egg cholesterol, plasma cholesterol, plasma triglyceride and histological changes of duodenum. Although, using the different levels of probiotic caused highly significant increase (P< 0.01) in goblet cell numbers, significant increase (P< 0.05) in destroying apical cells of villus and significant decrease (P< 0.05) in plasma cholesterol, plasma triglyceride and egg cholesterol (mg gr-1 of yolk), but it had no significant effects on other traits.